Microglial polarization dynamics in dorsal spinal cord in the early stages following chronic sciatic nerve damage. (23rd March 2016) - Xu, Fangting; Huang, Juan; He, Zhenghua; Chen, Jia; Tang, Xiaoting; Song, Zongbin; Guo, Qulian; Huang, Changsheng
Highlights: Microglial polarization dynamics remote from a primary nerve lesion were examined. Both M1 and M2 microglia were activated in the spinal cord one day after injury. Microglia skewed towards the M1 phenotype during the following seven and 14 days. Abstract: Peripheral nerve injury can lead to activation of spinal microglia, which can mediate neuroinflammation and contribute to neuropathic pain following nerve injury. Activated microglia may manifest with either pro-inflammatory M1 phenotype or anti-inflammatory M2 phenotype, which may lead to detrimental or beneficial roles in the nervous system. In this study, microglia numbers, morphology and gene profiles were examined in the dorsal spinal cord of rats over 14 days following sciatic nerve chronic constriction injury (CCI). The morphology of some microglia changed from a surveying to an activated state within 1 day of CCI. Neuropathic pain developed within seven to 14 days following injury and microglia numbers were increased, with almost all in the dorsal spinal cord morphologically defined as activated. At day one after CCI, both M1 and M2 microglia-related genes were increased but only M1 microglia-related genes remained elevated at day seven and 14 thereafter. These results indicate that both M1 and M2 microglia were activated in the dorsal spinal cord one day after CCI but the microglia skewed towards M1 phenotype during the following seven and 14 days.